Development of high infrared emissivity porous ceramic coating using pre-synthesized flower-like CeO2 powder for high temperature applications. Issue 1 (1st January 2022) - Han, Rifei; Tariq, Naeem ul Haq; Liu, Housheng; Zhao, Lijia; Luo, Jing; Wang, Jiqiang; Cui, Xinyu; Xiong, Tianying
Abstract: In this article, a unique high infrared emissivity porous ceramic coating was prepared by slurry spraying method. In the first step, flower-like CeO2 powder particles were synthesized by precursor pyrolysis method using Ce2 (CO3 )3 ·8H2 O as the transition phase. Subsequently, flower-like CeO2 ceramic particles (filler) and silicate (binder) were deposited by air spraying. The microstructure and phase composition of the prepared particles and the ceramic coating were examined using X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and X-ray diffraction (XRD). High temperature performance of the coating was assessed by conducting prolong isothermal oxidation and thermal shock tests. Infrared emissivity of the coating was tested at 750 °C by employing infrared radiation instrument. The prepared coating exhibited excellent high temperature resistance and high infrared emissivity (ε3-5μm  = 0.887, ε8-14μm  = 0.889 and ε2.5-19μm  = 0.893) at 750 °C. This was attributed to the presence of a large number of pores (within and among CeO2 particles) in the coating. In the end, possible mechanisms related with high infrared emissivity of the coating were discussed in detail. Graphical abstract: Image 1 Highlights: Unique flower-like CeO2 particles were synthesized by precursor pyrolysis method. Ceramic coating was prepared by air spraying using silicate and CeO2 particles. Prepared coating contains large number of pores due to unique structure of CeO2 . Coating resulted in high infrared emissivity due to multiple reflections at pores.